Estudio comparativo en cirugía perirradicular entre la técnica convencional y técnicas para la regeneración ósea - Tobón, Sergio; Marín, Martha; Mesa, Ana Lucía; Valencia, Javier; Arismendi-Echavarría, Jorge Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2009)
It was intended to demonstrate the ellicacy 01 two materials 01 bone regeneration as assisting towerds therapy in periradicular surgery and their effect on the healing 01periapical tissues. Twenty eight petients (30 surgical sites). were selected and distributed in three groups: group A, conventional technique; graup B, conventional technique plus non-bioabsorbable Gore'Iex" Augmentation membrane and group C, conventional technique plus membrane and synthetic hlling material type bioebsorbeble hydroxyapatite (Osteoüert"). Clinical and radiological evaluations were made right belore the initial sur¿;ery, a week later and every three months alter surgery up to twelve months. Two histological evaluations were performed (at the beginning and at 12months). The results showed complete clinical and radiographic healing (100%) lor group C, with histologic reports 01trabecular bone for all the cases For group B, a 66.66% 01the cases showed complete radiographic healing, incomplete in a 11.11% and uncertain in 22.22%, with histologic results 01 trabecular bone in 62.5%.. scer tissue in 12.5% and granuloma in 25% 01 the cases. For group A there was a complete radiographic healing in 44.44%, incomplete in 44.44% and unsuccesslul in 11.11%, with report 01 granuloma in 50%, scar tissue in 25% and trabecular bone in 25% 01 the cases. !t was concluded that the conventional technique presents a high probability 01relepse and that the use 01 bone regeneration materials improves the predictability 01clinicel, radiographic and histological healing.